Band gap Measurement of P – type Monocrystalline Silicon Wafer - Hashmi, G; Basher, MK; Hoq, M; Rahman, MH (Bangladesh Journal of Scientific and Industrial Research, 2018)
Band gap of P-type monocrystalline silicon wafer has been measured using spectral response measurement system. To see the spectral response a SR510 lock in amplifier, SR540 optical chopper, monochromator (400nm-1200nm), optical detector and lab view software has been used. From spectral response of polished P-type monocrystalline silicon wafer absorption, reflection and transmission has been respectively seen from 400nm-550nm, 550nm-1050nm and 1050-1200nm. Assuming band gap of silicon is (1.12eV), this result has been theoretically verified using Planck–Einstein relation. Moreover, theoretical band gap of silicon has been calculated (1.127362 eV). The band gap measurement process uses partial concept of Tauc’s downhill negative slop and Planck–Einstein relation. Experimental result shows that, the band gap of silicon is 1.127907 eV. Bangladesh J. Sci. Ind. Res.53(3), 179-184, 2018